2016
DOI: 10.1371/journal.pone.0160260
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Pulse Release Tablet for Amoxicillin: Preparation, Pharmacokinetic Study and Physiologically Based Pharmacokinetic Modeling

Abstract: BackgroundAmoxicillin is a commonly used antibiotic which has a short half-life in human. The frequent administration of amoxicillin is often required to keep the plasma drug level in an effective range. The short dosing interval of amoxicillin could also cause some side effects and drug resistance, and impair its therapeutic efficacy and patients’ compliance. Therefore, a three-pulse release tablet of amoxicillin is desired to generate sustained release in vivo, and thus to avoid the above mentioned disadvant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
(36 reference statements)
2
4
0
Order By: Relevance
“…Both the polymers were amorphous in nature, as shown in Figure 6. These SEM images of HP-β-CD and HPMC agreed with the research results described by Li et al (2016) and Novaḱ et al (2012). 34,35 AM appeared as a flat rod-shaped crystal, as presented in Figure 3.…”
Section: Preliminary Studies Of Sdssupporting
confidence: 91%
See 1 more Smart Citation
“…Both the polymers were amorphous in nature, as shown in Figure 6. These SEM images of HP-β-CD and HPMC agreed with the research results described by Li et al (2016) and Novaḱ et al (2012). 34,35 AM appeared as a flat rod-shaped crystal, as presented in Figure 3.…”
Section: Preliminary Studies Of Sdssupporting
confidence: 91%
“…“Solid dispersions” (SDs) are a vital approach to achieve a drug dispersed amorphously in a polymeric matrix. 34 Six different SDs (F1–F6) based on AM and polymers HP-β-CD and HPMC were prepared by spray drying. SDs (F1–F6) appeared as a yellowish off-white amorphous powder with sticky nature.…”
Section: Resultsmentioning
confidence: 99%
“…α,β-Unsaturated trifluoromethyl ketones 251 and trichloromethyl ketones 255 were also tested in the reaction with 595, in the presence of the same organocatalyst (S)-CXXXV (Scheme 248). 294,295 As expected, the attack occurred on the β-Re face of both trihalomethyl ketones, giving (R)-597 and (R)-598, respectively. The results were very similar in both the reactions, and the products were obtained within excellent…”
Section: Oxidative [3 + 3] N-hc-catalyzed Reaction Between Saturated ...supporting
confidence: 65%
“…Scheme 248. Enantioselective [Michael Reaction/Hemiacetalization] of Cyanoketones 595 with α,β-Unsaturated Trifluoromethyl Ketones251 and Trichloromethyl Ketones 255 Catalyzed by (S)-CXXXV294,295 …”
mentioning
confidence: 99%
“…In 2004, the pharmacokinetically enhanced amoxicillin/clavulanate (2000/125 mg) twice daily formulation demonstrated higher T >MIC values and was more effective than immediate release formulations, achieving substantially better eradication rates against S. pneumoniae isolates with MICs commonly encountered in the clinic [56]. More recently, Li et al [57] evaluated a three-pulse release tablet for amoxicillin using a physiologically based pharmacokinetic modeling (PBPK) and they also concluded that their formulation extended the effective plasma concentration compared to the immediate release tablet. In veterinary medicine, with the same aim, Horwitz et al developed a novel gastroretentive controlled-release drug delivery system for amoxicillin therapy [58].…”
Section: Pk/pd Analysis In Drug Developmentmentioning
confidence: 99%